Proceedings of the 15th ACM on International Conference on Multimodal Interaction 2013
DOI: 10.1145/2522848.2522851
|View full text |Cite
|
Sign up to set email alerts
|

Learning a sparse codebook of facial and body microexpressions for emotion recognition

Abstract: Obtaining a compact and discriminative representation of facial and body expressions is a difficult problem in emotion recognition. Part of the difficulty is capturing microexpressions, i.e., short, involuntary expressions that last for only a fraction of a second: at a micro-temporal scale, there are so many other subtle face and body movements that do not convey semantically meaningful information. We present a novel approach to this problem by exploiting the sparsity of the frequent micro-temporal motion pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Using the non-parametric Wilcoxon test, we found that the difference between correlations resulted from LSTM-RNN and CCRF is not significant, however, RMSE is significantly lower for LSTM-RNN (p < 1E − 4). Although, direct comparison of the performance is not possible with the other work due to the difference in the nature of the databases, the best achieved correlation is in the same range as the result of [46], the winner of AVEC 2012 challenge, on valence and superior to the correlation value reported on valence in a more recent work, [47]. Unfortunately, the previous papers on this topic did not report the standard deviation of their results; thus its comparison was impossible.…”
Section: Continuous Emotion Detectionmentioning
confidence: 75%
“…Using the non-parametric Wilcoxon test, we found that the difference between correlations resulted from LSTM-RNN and CCRF is not significant, however, RMSE is significantly lower for LSTM-RNN (p < 1E − 4). Although, direct comparison of the performance is not possible with the other work due to the difference in the nature of the databases, the best achieved correlation is in the same range as the result of [46], the winner of AVEC 2012 challenge, on valence and superior to the correlation value reported on valence in a more recent work, [47]. Unfortunately, the previous papers on this topic did not report the standard deviation of their results; thus its comparison was impossible.…”
Section: Continuous Emotion Detectionmentioning
confidence: 75%
“…Therefore, we conclude that the LSTM-RNN performed the best in this setting and with the goal of continuous valence detection. Although direct comparison of the performance is not possible with the other works due to the difference in the nature of the databases, the best achieved correlation is in the same range as the result of [23], the winner of AVEC 2012 challenge, on valence and superior to the correlation value reported on valence in a more recent work, [24]. Unfortunately, the previous papers on this topic did not report the standard deviation of their results; thus its comparison was impossible.…”
Section: Continuous Emotion Detectionmentioning
confidence: 83%
“…Recently, Song et al [12] used them to encode facial and body micro expressions for emotion detection. They reflect interesting events that can be used for a compact representation of video data as well as for its interpretation.…”
Section: ) Space Time Interest Point (Stip)mentioning
confidence: 99%
“…They reflect interesting events that can be used for a compact representation of video data as well as for its interpretation. We used the approach proposed by Song et al [12]. STIP capture salient visual patterns in a space-time image volume by extending the local spatial image descriptor to the space-time domain.…”
Section: ) Space Time Interest Point (Stip)mentioning
confidence: 99%